Factors Analysis Of Failure And Reliability Of Electric Functions In Steel Production Processes Using FMEA, FTA, RCA And RBD At PT. Growth Sumatra Industry Medan-North Sumatera - Hendra Saputra Banjarnahor (Institute of Computer Science (IOCS), 2021)
When a machine has a high failure rate, it is necessary to analyze the causes of the failure to the root of the problem so as to determine the appropriate action to improve the performance of a machine.PT Growth Sumatra Industry is a company engaged in steelmaking industry.In the steelmaking line required electric arc furnace machine, continuous casting and rolling mill.The purpose of this research is to identify the factors causing failure and reliability analysis of electric arc furnace using Failure Mode and Effect Analysis (FMEA) method, Fault Tree Analysis (FTA), Root Cause Analysis (RCA) and Reliability Block Diagram (RBD). The application of FMEA analysis can determine the extent to which failure rates occur. Then proceed with the FTA to find out more about the underlying causes of a failure. Then use RCA to find out the real problem that is the main cause of the high loss by making a fishbone diagram. And the latter determines the value of system reliability by using RBD based on trace failure. The object of this research is electric arc furnace machine. Data retrieval was obtained with interview result and maintenance record conducted by company. The data obtained is then analyzed descriptively ie retrieval of data maintenance from the company, the results of data processing included in the table , and displayed in graphical form. The result of the research was obtained by FMEA method obtained RPN value on each of the highest component that is furnace shell body with value reach 180. Then analysis using FTA method got the probability value of system failure period of January 2016 - December 2016 reached 36.94%.